Perilaku Kepemimpinan Kontingensi Kiai dalam Memanajerial Pondok Pesantren Al-Ittihad Lembung Timur Lenteng Sumenep - Ali Rahmat; Fika Fitrotin Karomah (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2019)
The results of this research showed that the community's views on kiai's leadership turned out to provide positive responses and meanings. This is certainly influenced by the skills of the kiai in managing Pondok Pesantren Al-Ittihad, caring about the interests of the community, and their participation in social society. The kiai’s leadership practice appear in the clear and structured division of tasks, tolerance and full trust. So that boarding school (pesantren) officials like the leadership style of kiai because kiai are also very skilled in applying different leadership models according to situations and conditions. The factors that influence Kiai's leadership include environmental factors, educational background, and experience factors